1989
DOI: 10.1182/blood.v74.5.1563.bloodjournal7451563
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and partial purification of human marrow cells capable of initiating long-term hematopoiesis in vitro

Abstract: To develop a purification strategy for isolating the most primitive hematopoietic stem cells present in normal human marrow we have combined cell separation techniques with an assay for cells that initiate sustained hematopoiesis in vitro in the presence of irradiated human marrow adherent cells. These “feeders” were established by subculturing 2- to 6-week-old primary long-term marrow culture adherent layers at a density of 3 x 10(4) irradiated cells per square centimeter. Test “long-term culture (LTC)-initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
99
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 0 publications
2
99
0
2
Order By: Relevance
“…Long-term bone marrow culture (LTBMC). Ten thousand sorted CD34 1 IL-6R 1 or IL-6R 2 cells were plated on allogeneic irradiated bone marrow (BM) stromal layers cultured in stromal medium [a-medium, 10% FCS, 10% horse serum (Bio Whittaker, Walkersville, MD, USA), 5 Â 10 25 mol/l 2-ME and 10 26 mol/l hydrocortisone (Japan Upjohn, Tokyo, Japan)], according to the reported method with minor modifications (Sutherland et al, 1989;Gunji et al, 1993;Sakabe et al, 1998).…”
Section: Recombinant Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term bone marrow culture (LTBMC). Ten thousand sorted CD34 1 IL-6R 1 or IL-6R 2 cells were plated on allogeneic irradiated bone marrow (BM) stromal layers cultured in stromal medium [a-medium, 10% FCS, 10% horse serum (Bio Whittaker, Walkersville, MD, USA), 5 Â 10 25 mol/l 2-ME and 10 26 mol/l hydrocortisone (Japan Upjohn, Tokyo, Japan)], according to the reported method with minor modifications (Sutherland et al, 1989;Gunji et al, 1993;Sakabe et al, 1998).…”
Section: Recombinant Factorsmentioning
confidence: 99%
“…The significance of differences between mean values was determined using the two-tailed Student's t-test. The frequency of LTC-ICs in the initial cell population was calculated by Poisson statistics, as reported elsewhere (Taswell, 1981;Sutherland et al, 1989).…”
Section: Recombinant Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal haematopoiesis occurs as the result of the ordered proliferation and differentiation of a hierarchy of progenitors, which have been categorized by their functional potential as measured by in vitro and in vivo assays (Lord & Spooncer, 1986;Andrews et al, 1989;Sutherland et al, 1989a;Jones et al, 1990;Larochelle et al, 1996). In acute myeloid leukaemia (AML), only a subset of leukaemic cells are capable of proliferation in methylcellulose (Moore et al, 1973;Minden et al, 1979), suggesting that AML blasts are heterogeneous in their proliferative potential, at least in vitro.…”
mentioning
confidence: 99%
“…These studies have suggested that such cells exist in AML, and that they are phenotypically distinguishable from the majority of blasts and AML colony-forming cells (Lapidot et al, 1994;Sutherland et al, 1996;Ailles et al, 1997;Blair et al, 1997Blair et al, , 1998Bonnet & Dick, 1997;Blair & Sutherland, 2000). As longterm (5±8 week) growth in in vitro assays is important to detect the most primitive normal progenitors, (Sutherland et al, 1989a(Sutherland et al, , 1990Hao et al, 1996), we reasoned that longterm in vitro assays may also detect primitive AML progenitors. Initially, we evaluated 2±8 week production of colony-forming units (CFU) from growth factor containing suspension cultures (SC) in the absence of stroma as a quantitative assay for the more primitive AML progenitors.…”
mentioning
confidence: 99%